(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
A Brief History of Religious Tolerance/Freedom.The article traces how the idea of tolerance in general, and religious tolerance in particular, has evolved in history. We will note that although the Bible is among the earliest books of mankind, it contains extremely valuable advice on this topic, being by far the Book of Books. Certain historical periods combined with the dawn of pre-modernity have stagnated and involuted from the point of view of the tolerance granted to the other different from us. To the surprise of many, while medieval Europe faced the iron hand of the Inquisition, on the shores of the Bosphorus Christian dissidents could live out their lives in return for paying a religious tax prescribed by the Koran. Under the same Ottoman auspices, the first act of tolerance in the world was issued, in Turda, in 1568, being succeeded by the Act of Tolerance in 1689, from which fundamental human rights emerged later.